Fast discharge and high energy density of nanocomposite capacitors using Ba0.6Sr0.4TiO3 nanofibers. Issue 13 (October 2016) - Pan, Z.B.; Yao, L.M.; Zhai, J.W.; Liu, S.H.; Yang, K.; Wang, H.T.; Liu, J.H.
Abstract: Nanocomposites combining high breakdown strength (BDS) polymer and high dielectric permittivity ceramic fillers have shown great potential for pulsed power application. Here a new composite material based on surface-functionalized Ba0.6 Sr0.4 TiO3 nanofibers/poly(vinylidene fluoride) (BST NF/PVDF) has been prepared by solution casting. The nanocomposites containing 2.5 vol% isopropyl dioleic(dioctylphosphate) titanate (NDZ 101)-functionalized BST NF (N-h-BST NF) have large energy density of 6.95 J cm −3 at 380 MV m −1, which is 1.85 times larger than that of the pure PVDF at the same electric field. Also, the discharge speed of the nanocomposites containing 7.5 vol% N-h-BST NF is approximately 0.11 μs. The good properties, together with the large energy density and fast discharge speed, make this material a promising candidate for pulsed power capacitor.